Conversor CA-CC monofásico bidirecional isolado aplicado como carregador de baterias de veículos elétricos - Souza, José Janiere Silva de (2020)
This paper proposes the use of a bi-directional AC-DC converter single-phase isolated as a battery charger for an electric vehicle for agricultural applications. In constructive terms, the topology is based on the Dual Active Bridge (DAB) converter. The primary side consisting of two arms of the three-level Neutral Point Clamped (NPC) converter, through the use of an autotransformer, in order to form a Multi-State Switching Cells (MSSC), while the secondary side comprises a Full Bridge (FB) converter galvanically isolated from the primary side using a high frequency transformer. During qualitative analysis shows the states of switching and modulation strategy used. In the quantitative analysis, the expressions that define the synthesized voltages and their respective waveforms stand out, in addition to the studies of the operation with correction of the power factor, the ripple of the input current and the power flow. In order to implement a prototype powered by a power supply 220 V, 60 Hz and 56 V output voltage are shown the designs of the controllers as well as the magnetic elements and the measuring circuits, conditioning and filtering system variables that will be controlled. The validation of the theoretical and the physical design of the building elements is made using computer simulations when operating in permanent and dynamic regime. In addition, experimental results are presented for the primary side of the converter through the use of a 750 W prototype at full load considering its operation in Grid to Vehicle mode in permanent and dynamic regime.